Pyropia orbicularis sp. nov. (Rhodophyta, Bangiaceae) based on a population previously known as Porphyra columbina from the central coast of Chile - Ramirez, Maria Eliana; Contreras-Porcia, Loretto; Guillemin, Marie-Laure; Brodie, Juliet; Valdivia, Catalina; Flores-Molina, Maria Rosa; Nuñez, Alejandra; Bulboa Contador, Cristian; Lovazzano, Carlos (Phytotaxa, 2014)
A new species of bladed Bangiales, Pyropia orbicularis sp. nov., has been described for the first time from the central coast of Chile based on morphology and molecular analyses. The new species was incorrectly known previously as Porphyra columbina (now Pyropia columbina), and it can be distinguished from other species of Pyropia through a range of morphological characteristics, including the shape, texture and colour of the thallus, and the arrangement of the reproductive structures on the foliose thalli. Molecular phylogenies based on both the mitochondrial COI and plastid rbcL gene regions enable this species to be distinguished from other species within Pyropia. P. orbicularis sp. nov. belongs to a well-supported clade of Pyropia from the southern oceans that include specimens from the South Pacific (North, South, Chatham, Stewart, Auckland, and Campbell Island, New Zealand, New South Wales, and Macquarie Island, Australia) including P. columbina and P. plicata. Within this clade, the highest sequence identity was observed between Pyropia orbicularis sp. nov. and Pyropia sp. FIC from the Falkland Islands.